2016
DOI: 10.4103/0019-5545.196708
|View full text |Cite
|
Sign up to set email alerts
|

Distressing cutaneous lesion among bipolar affective disorder patients on lithium therapy: A retrospective cross-sectional study

Abstract: Aim:To assess the incidence of cutaneous lesion in bipolar affective disorder (BPAD) patients on lithium therapy. To evaluate the relationship between duration of lithium therapy, dosage of lithium, serum lithium level, and cutaneous lesions. To assess whether reduction/stoppage of dose of lithium has any change in the course of cutaneous side effects. To look for a relationship between addition of isotretinoin and the course of mood disorder.Methodology:We retrospectively collected hospital case records of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These effects correlate directly with the dose of lithium and therapeutic range of serum lithium. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…These effects correlate directly with the dose of lithium and therapeutic range of serum lithium. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…6 Prevalence of our study was similar to a study conducted in India where 77% of psychiatric patients showed dermatological disorders. 7 This study concluded that out of psychiatric patients having dermatological diseases, a majority 62% were females and 38% were males. This also bore resemblance to studies conducted in Cairo, Egypt where the majority 61% were females, 1 in India 58.1% 4 and in contrast to a study conducted in Lahore where female psychiatric patients having dermatological diseases were only 39.4%.…”
Section: Discussionmentioning
confidence: 90%
“…The chemical lithium, which psychiatrists prescribe to treat bipolar affective disorders, has the highest rate of cutaneous side effects of any psychoactive substance [1]. The most frequent cutaneous responses to lithium include acneiform eruptions, psoriasis, maculopapular eruptions, and follicular eruptions [2][3][4]. The exact mechanism by which lithium causes these reactions is yet not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, safety concerns throughout the treatment remain significant due to its narrow therapeutic window and major side effects like hypothyroidism and cardiac and renal dysfunction; thus, it requires monitoring. Common side effects include gastrointestinal symptoms like nausea, diarrhea, urinary system problems like increased urinary frequency, and excessive thirst [ 4 ]. Weight gain and impaired cognition tend to be more stressful to the patients and may contribute to poor medication adherence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%